Foreign Aid and Government Legitimacy. Issue 2 (25th March 2015) - Dietrich, Simone; Winters, Matthew S.
Abstract: Branding of foreign aid may undermine government legitimacy in developing countries when citizens see social services being provided by external actors. We run a survey experiment on a sample of Indian respondents. All subjects learn about an HIV/AIDS program; treated subjects learn that it was foreign-funded. We find null results that, along with existing results in the literature obtained from observational data, call into question the view that foreign-funded service delivery interferes with the development of a fiscal contract between the state and its citizens.